Automated Long-Term EEG Review: Fast and Precise Analysis in Critical Care Patients - Koren, Johannes P.; Herta, Johannes; Fürbass, Franz; Pirker, Susanne; Reiner-Deitemyer, Veronika; Riederer, Franz; Flechsenhar, Julia; Hartmann, Manfred; Kluge, Tilmann; Baumgartner, Christoph (Frontiers in Neurology, 2018)
Background Ongoing or recurrent seizure activity without prominent motor features is a common burden in neurological critical care patients and people with epilepsy during ICU stays. Continuous EEG (CEEG) is the gold standard for detecting ongoing ictal EEG patterns and monitoring functional brain activity. However CEEG review is very demanding and time consuming. The purpose of the present multirater, EEG expert reviewer study, is to test and assess the clinical feasibility of an automatic EEG pattern detection method (Neurotrend). Methods Four board certified EEG reviewers used Neurotrend to annotate 76 CEEG datasets à six hours (in total 456 hours of EEG) for rhythmic and periodic EEG patterns (RPP), unequivocal ictal EEG patterns and burst suppression. All reviewers had a predefined time limit of five minutes (± two minutes) per CEEG dataset and were compared to a predefined gold standard (conventional EEG review with unlimited time). Subanalysis of specific features of RPP was conducted as well. We used Gwet’s AC1 and AC2 coefficients to calculate interrater agreement (IRA) and multirater agreement (MRA). Also, we determined individual performance measures for unequivocal ictal EEG patterns and burst suppression. Bonferroni-Holmes correction for multiple testing was applied to all statistical tests. Results Mean review time was 3.3 minutes (± 1.9 min) per CEEG dataset. We found substantial IRA for unequivocal ictal EEG patterns (0.61 – 0.79; mean sensitivity 86.8%; mean specificity 82.2%, p<0.001) and burst suppression (0.68 – 0.71; mean sensitivity 96.7%; mean specificity 76.9% p<0.001). Two reviewers showed substantial IRA for RPP (0.68 – 0.72), whereas the other two showed moderate agreement (0.45 – 0.54), compared to the gold standard (p<0.001). MRA showed almost perfect agreement for burst suppression (0.86) and moderate agreement for RPP (0.54) and unequivocal ictal EEG patterns (0.57). Conclusions We demonstrated the clinical feasibility of an automatic critical care EEG pattern detection method on two levels: 1) reasonable high agreement compared to the gold standard, 2) reasonable short review times compared to previously reported EEG review times with conventional EEG analysis.